EFUSI PLEURA DAN PNEUMOTHORAKS - Sari Nikmawati (Yayasan Nusantara Hasana Berdikari, 2026)
Pleural Effusion and Pneumothorax are pleural cavity disorders that can cause respiratory impairment and decreased lung function. Pleural effusion occurs due to the accumulation of fluid within the pleural cavity and may be caused by heart failure, infection, malignancy, or other systemic diseases. Meanwhile, pneumothorax is a condition characterized by the presence of air in the pleural space leading to partial or complete lung collapse, and it may occur spontaneously, traumatically, or iatrogenically. Clinical manifestations of both conditions include shortness of breath, chest pain, cough, and decreased breath sounds on the affected side. Diagnosis is established through history taking, physical examination, and supporting investigations such as chest radiography, ultrasonography, or thoracic CT scan. Management depends on the underlying cause and severity of the disease, ranging from observation and medical therapy to thoracentesis, chest tube insertion, and surgical intervention. Early diagnosis and appropriate management are essential to prevent complications and improve patient outcomes.